SOME PROPERTIES OF HIGH PERFORMANCE CARBON FIBRES CEMENT COMPOSITES (Journal of Engineering, 2009)
The paper presents properties of high performance concrete reinforced with relatively high percentage of choped carbon fibers vol. fraction ranging from (1 to 5) %. The great advantage of such composites is their relatively high flexural strength. A low water to cement ratio of 0.3 with super plasticizer was used in order to keep the cement mix easily workable. To improve the properties, a locally existing pozzolan based on reactive meta- kaolin was used in the mixture together with silica sand. A high modulus carbon fibers (450 KN/mm2) were also used. In addition to the flexural strength, dynamic modulus of elastisity were found using dynamic methods.The results showed that the specimen failed in flexureal by a single crack although the ultimate tensile strength and the stiffness of the composite were increased as the fibers content was increased.